Self-help group as a method to improve emotion regulation in bullied students - Azalia, Lavenda; Rr. Indahria, Sulistyarini (Penerbit Universiti Kebangsaan Malaysia, 2019)
Bullying is a phenomenon that can happen to everyone. Bullying victims’ mental health can be negatively impacted. It can make victims experience emotional, psychosomatic and psychosocial problems. Adolescents who experience bullying are at greater risk of being hampered in managing or regulating their emotions. Self-help groups are given as a solution for intervention. This study aims to provide self-help group interventions to eight senior high school students aged 15 to 17 years with two males and six females indicated to be victims of bullying and experiencing interference with regulation of their emotions. The pretest and posttest in this study used the emotional regulation scale. Data were analyzed using the Wilcoxon test. The result obtained was 0.012 which means that there is an increase in regulation of emotions to all participants after being given a self-help group. The participants said that they felt more understanding, calm, and more able to control themselves after the intervention. The existence of a new support system also makes them feel more comfortable to be open about their problems because they do not feel alone.